ANALYSIS HYBRID CONTRACCTS ON GOLD PAWN TAKE OVER FINANCING (Study on BSI KCP Sumenep Trunojoyo 1) - Nurul Hidayati; Nur Eka Mutmainnah (Journal Of Business, Finance, and Economics (JBFE), 2023)
The contracts used in contemporary Islamic financial institutions are now more complicated than before, so it takes development from the Hybrid Contract. The problem raised in this study is What is the analysis of the implementation of gold pawning take over financing, How is the legality of taking ujrah in gold mortgage take over financing. To find out more about the phenomenon of the Hybrid Contract on the take over of the pawning gold, then the researcher used a qualitative research approach, the method used is the method of interviews, observation, and documentation. From this method, then researchers process and analyze to obtain data or information. The subjects of this study were taken from the BOMS section, 2 pawning staff of gold pawnshops, and 2 customers. for the validity of the data, researchers used triangulation in two ways, namely: comparing observational data with the results of interviews with inter-method triangulation, namely comparing one person's situation and perspective with various opinions and views of other people. The implementation implemented at BSI KCP Sumenep Trunojoyo 1 includes gold pawn take over financing, namely: The use of rahn, qard{, and ija>rah contracts, as the application of the Hybrid Contract (multi contract). The results of the study show that, in the implementation of gold pawning take over at BSI, the criteria are rahn care, given to the pawn recipient, until the ija>rah contract arose and was contracted in duplicate with the rahn contract. Thus it will cause two contracts in one transaction which is not allowed in Islamic teachings. However, in the legality of taking his ujrah fee in the financing of the gold mortgage take over at the BSI, it is determined based on the type of gold and also the weight of the gold. Not determined based on the amount of financing.